If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(x + -2) + -5(3 + -2x) = 5(x + 1) + -3 Reorder the terms: -4(-2 + x) + -5(3 + -2x) = 5(x + 1) + -3 (-2 * -4 + x * -4) + -5(3 + -2x) = 5(x + 1) + -3 (8 + -4x) + -5(3 + -2x) = 5(x + 1) + -3 8 + -4x + (3 * -5 + -2x * -5) = 5(x + 1) + -3 8 + -4x + (-15 + 10x) = 5(x + 1) + -3 Reorder the terms: 8 + -15 + -4x + 10x = 5(x + 1) + -3 Combine like terms: 8 + -15 = -7 -7 + -4x + 10x = 5(x + 1) + -3 Combine like terms: -4x + 10x = 6x -7 + 6x = 5(x + 1) + -3 Reorder the terms: -7 + 6x = 5(1 + x) + -3 -7 + 6x = (1 * 5 + x * 5) + -3 -7 + 6x = (5 + 5x) + -3 Reorder the terms: -7 + 6x = 5 + -3 + 5x Combine like terms: 5 + -3 = 2 -7 + 6x = 2 + 5x Solving -7 + 6x = 2 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -7 + 6x + -5x = 2 + 5x + -5x Combine like terms: 6x + -5x = 1x -7 + 1x = 2 + 5x + -5x Combine like terms: 5x + -5x = 0 -7 + 1x = 2 + 0 -7 + 1x = 2 Add '7' to each side of the equation. -7 + 7 + 1x = 2 + 7 Combine like terms: -7 + 7 = 0 0 + 1x = 2 + 7 1x = 2 + 7 Combine like terms: 2 + 7 = 9 1x = 9 Divide each side by '1'. x = 9 Simplifying x = 9
| L^2-23L=90 | | (x^2-y^3)(x^2+y^3)(x^4+y^6)= | | 0.9a=0.6a | | 3x-18=36 | | 2x-4=3x+1 | | 6=2a+11 | | -3(x-1)+8(x-3)=6x+7-5 | | 8(3-x)=-2(x+5) | | -2(n-5)-(3n-5)=-6n | | -9(v+3)+2v+7=8v+6 | | x(3x^2-23)=8 | | 4(x-3)(x+3)(x^2+9)= | | 4w^6+24w^5+36w^4= | | 3v+-v=-4 | | 2a=2a-11 | | 4x^3+4x^2-9x-9=0 | | 2m^2-15m+13=0 | | 2m^2-15m+13=0 | | 2(3x-8)=5(2-x) | | (2x^2-19x+24)=0 | | 2(2x^2-19x+24)=0 | | 3w^2+7w+2=0 | | (d+3)4=(d+12)3 | | -8(v+4)+3v+6=8v+7 | | 9-2[6-(9y-2)]= | | u^4+8u^3+20u^2= | | 13-9x=5-x | | 2(2x^2-19+24)=0 | | 2w^2+3w=54 | | 9-(2x-5)=3-3x | | (9x-11)(9x-11)=99 | | 1-y/3=6 |